Recent sedimentation in an Amazon tidal tributary: Integrated analysis of morphology and sedimentology. (April 2021) - Silva, Ariane M.M.; Asp, Nils E.; Gomes, Vando J.C.; Braga, Antonia A.; Gomes, José D.; Fricke, Aaron T.; Souza-Filho, Pedro Walfir M.; Souza, Thiago P.; Almeida, Pryscilla D.; Ogston, Andrea S.; Nittrouer, Charles A.
Abstract: The Xingu River is an important tributary of the Amazon River, contributing 5% of its total water discharge. Nevertheless, it does not contribute substantially to the sediment load. The lower reach of the Xingu River forms a ria, a result of the Holocene sea-level rise. The Xingu is also classified as a tidal river, with tides >1 m at its confluence with the Amazon River. This study evaluated the morphology and sedimentology of the area, correlating both with hydrodynamics to understand the infilling process of the Xingu ria. The study area encompasses a stretch of ~160 km, between the Xingu–Amazon confluence and the narrowing of the fluvial channel. During the season of maximum sediment-discharge of the Amazon River (i.e., Feb 2016), 109 bottom sediment samples were collected. Eleven of the sampling sites were re-sampled during the minimum water-discharge period of both rivers (i.e., Nov 2016). During the maximum water-discharge period of the Amazon River (i.e., Jun 2018), additional water-level measurements were undertaken simultaneously at several locations along the Xingu River. The ria morphology was evaluated on the basis of the bathymetric surveys of the Brazilian Navy (DHN). The results show that the infilling process of the ria has taken place from both the upstream and downstream directions. From upstream, the Xingu River is forming a prominent bayhead delta. From the Xingu-Amazon River confluence, tides have transported Amazon River sediments into the Xingu Ria. There is a central portion of the ria lake with a large cross-sectional area, where relatively small amounts of muddy sediments are accumulating in a quiescent environment. Sands prevail along the lateral margins, where wave action causes bluff erosion and limits fine-sediment deposition. Sands are also common in the bayhead delta and the confluence areas. Results suggest that the sediment input from the Amazon River into the Xingu ria has been reduced over time, likely as result of a reduction in tidally driven flux from the Amazon River into the Xingu River, which has occurred with a gradual increase in the constriction of the confluence as Amazon floodplains prograde. Highlights: The Xingu is a tidal river, with tides >1 m at its confluence with the Amazon River. Valley incision and subsequent drowning resulted in a ria-lake morphology Infilling process has taken place from both upstream and downstream directions Large accommodation space remains at central portion, within diatom sedimentation Morphology and tide-driven transport favor sediment entrapment from different source